Allosteric changes in HDM2 by the ATM phosphomimetic S395D mutation: implications on HDM2 function. Issue 21 (15th November 2019) - Uhrik, Lukas; Wang, Lixiao; Haronikova, Lucia; Medina-Medina, Ixaura; Rebolloso-Gomez, Yolanda; Chen, Sa; Vojtesek, Borivoj; Fahraeus, Robin; Hernychova, Lenka; Olivares-Illana, Vanesa
Abstract : Allosteric changes imposed by post-translational modifications regulate and differentiate the functions of proteins with intrinsic disorder regions. HDM2 is a hub protein with a large interactome and with different cellular functions. It is best known for its regulation of the p53 tumour suppressor. Under normal cellular conditions, HDM2 ubiquitinates and degrades p53 by the 26S proteasome but after DNA damage, HDM2 switches from a negative to a positive regulator of p53 by binding to p53 mRNA to promote translation of the p53 mRNA. This change in activity is governed by the ataxia telangiectasia mutated kinase via phosphorylation on serine 395 and is mimicked by the S395D phosphomimetic mutant. Here we have used different approaches to show that this event is accompanied by a specific change in the HDM2 structure that affects the HDM2 interactome, such as the N-termini HDM2–p53 protein–protein interaction. These data will give a better understanding of how HDM2 switches from a negative to a positive regulator of p53 and gain new insights into the control of the HDM2 structure and its interactome under different cellular conditions and help identify interphases as potential targets for new drug developments.